Skewed Forward-Looking Monetary Policy Behavior: A Look at the Latin American Inflation Targeting Practice - Vega, Marco (Pontificia Universidad Católica del Perú. CENTRUM, 2010)
Estimation of forward-looking interest rate rules is ubiquitous in the context of developed-economy central banks. In this paper, the five countries in Latin America that have adopted the Inflation Targeting framework are considered, and estimations of forward-looking policy rules are performed via i) standard least-squares criteria and ii) quantile regressions. The estimated standard mean effects indicate that Brazil, Chile, and Mexico are strongly forward-looking for horizons of a year and more. The estimated quantile effects suggest that policy makers in Brazil, Chile, and Mexico are likely to have faced more upside than downside risks to their one-year-ahead inflation forecasts when setting their policies.
Keywords: Monetary Policy; Quantile Regressions; https://purl.org/pe-repo/ocde/ford#5.02.04